Ecological evidence links adverse biological effects to pesticide and metal contamination in an urban Australian watershed. Issue 2 (4th February 2014) - Kellar, Claudette R.; Hassell, Kathryn L.; Long, Sara M.; Myers, Jackie H.; Golding, Lisa; Rose, Gavin; Kumar, Anupama; Hoffmann, Ary A.; Pettigrove, Vincent; Arnott, Shelley
Summary Aquatic ecosystems near urban areas are often ecologically impaired, but causative factors are rarely identified. Effects may be revealed by considering multiple lines of evidence at different levels of biological organization. Biological impairment is evident in the urban section of the Upper Dandenong Creek Catchment (Victoria, Australia). We assessed whether episodic sewage spills or other pollutants were the cause of poor ecological condition in the stream. The evidence evaluated included chemical and invertebrate assessments, caging studies of mudsnails Potamopyrgus antipodarum, antioxidant biomarkers and endocrine disruption‐related endpoints in fish (Carassius auratus and Gambusia holbrooki) and toxicological studies with chironomids (Chironomus tepperi). A combination of metals and pesticides is likely to be affecting the aquatic fauna across all biological levels, with macroinvertebrate communities, P. antipodarum and C. tepperi populations and C. auratus individuals all ecologically impaired. Adverse alterations to aquatic fauna were consistently seen in Bungalook Creek and persisted downstream of this confluence into Dandenong Creek. In addition, chemical assessments and toxicity identification evaluation (TIEs) resulted in several point sources of both metals and pesticides being identified as origins of impairment. This contrasted with an expectation that adverse effects were likely to be associated with sewer‐related pollution. As a consequence, target areas and specific pollutants were identified for remediation instead of an expensive sewer upgrade. Synthesis and applications. The results demonstrate that it is important to investigate biological effects in different taxa, in both the laboratory and field, to understand which stressors are causing adverse effects on faunal assemblages. When adverse effects are seen across multiple levels of biological organization and caused by the same pollutant from an identifiable source, there is a clear remedial path for managers.